I live in the slums : stories - Canxue, 1953- (Margellos world republic of letters book., 2020)
Combining elements of both Chinese materiality--the love of physical things--and Western abstract thinking, Can Xue's stories invite her readers into an immersive landscape that blends reality and illusion, mixes the physical and spiritual, and probes the space between consciousness and unconsciousness.